The use of uterine compression sutures in the management of patients with severe postpartum haemorrhage in a regional obstetric hospital - Muavha, Dakalo Arnold (Department of Obstetrics and Gynaecology, 2018)
Background: Postpartum haemorrhage (PPH) is a direct leading cause of maternal death in developing countries including South Africa, and atonic uterus is responsible for up to 80% of cases of postpartum haemorrhage. The introduction of the uterine compression suture (UCS) by C B-Lynch revolutionised the conservative surgical management of postpartum haemorrhage. Its use is simple, does not require special training and reduces the need for hysterectomy. Many small studies have been conducted in different parts of the world on its effectiveness but no published studies have been found from Africa. To understand the unique challenges in developing countries, especially those in Africa, it would be relevant to establish if uterine compression sutures are beneficial in a low resource setting for the management of PPH. Accordingly, the aim of the present study was to audit the use of uterine compression suture (UCS) in our regional hospital, with a focus on the circumstances in which it was used and its success rate in treating postpartum haemorrhage. Methods: This was a retrospective folder review study of all women who had a UCS inserted to treat obstetric haemorrhage in Mowbray Maternity Hospital during the period between January 2010 and June 2016, following ethical approval from the UCT HREC and Mowbray Maternity Hospital's management. Cases were identified from theatre registrars and a designated UCS book. Patients' records were retrieved and data collected and analyzed using the Excel spreadsheet software. Results: During the 6.5-year study period, there were 132, 612 deliveries in the population served by Mowbray maternity Hospital, of which 102,261 (78%) were by normal vaginal delivery and 30,351 (22%) by caesarean section. A total of 150 UCS cases were identified giving a rate of 0.87 UCS per 1000 deliveries (at MMH and its referral MOUs). Of the 150 cases, 115 (77%) patient files could be retrieved for further analysis. UCS was performed more commonly after ceasarean section (107; 93%) than after vaginal delivery (8; 7%) The majority were performed by obstetric registrars (73; 63.4%) compared to 21 (18.3%) performed by consultants and by medical officers. The UCS was successful in stopping haemorrhage without the need for hysterectomy in 107 (93%) of all analyzed cases. Among the 8 failures, all required a hysterectomy and one woman died. The majority of UCS (50%) were performed in cases with estimated blood loss over 1000 mls, with 20.9% having blood loss more than 2000mls. Of note, 13.9% had an estimated blood loss (EBL) less than 500 mls (the majority of which were performed by medical officers). Short term morbidity of UCS cases included blood transfusion (42%), admission to ICU (8.7%), post ceasarean section sepsis (9.6%), and prolonged hospital stay (46.1%). Discussion and conclusion: This study is one of the largest case series and the first done in an African setting. Our success rate of 93% is similar to other previously reported published studies with similar low rates of short term morbidity. Our study confirmed that the success of the UCS is achievable even in low-resource environments and that UCS can be safely performed by surgeons with different levels of surgical expertise (medical officers as well as registrars and consultants).